Mice lacking angiotensin type 2 receptor exhibit a sex-specific attenuation of insulin sensitivity - Quiroga, Diego Tomás (2019)
The renin-angiotensin system modulates insulin action. Pharmacological stimulation of angiotensin type 2 receptor (AT2R) was shown to have beneficial metabolic effects in various animal models of insulin resistance and type 2 diabetes and also to increase insulin sensitivity in wild type mice. In this study we further explored the role of the AT2R on insulin action and glucose homeostasis by investigating the glycemic profile and in vivo insulin signaling status in insulin-target tissues from both male and female AT2R knockout (KO) mice. When compared to the respective wild-type (WT) group, glycemia and insulinemia was unaltered in AT2RKO mice regardless of sex. However, female AT2RKO mice displayed decreased insulin sensitivity compared to their WT littermates. This was accompanied by a compensatory increase in adiponectinemia and with a specific attenuation of the activity of main insulin signaling components (insulin receptor, Akt and ERK1/2) in adipose tissue with no apparent alterations in insulin signaling in either liver or skeletal muscle. These parameters remained unaltered in male AT2RKO mice as compared to male WT mice. Present data show that the AT2R has a physiological role in the conservation of insulin action in female but not in male mice. Our results suggest a sexual dimorphism in the control of insulin action and glucose homeostasis by the AT2R and reinforce the notion that pharmacological modulation of the balance between the AT1R and AT2R receptor could be important for treatment of metabolic syndrome and type 2 diabetes.